Integrative biomechanics and physiology in c-c skiing - Holmberg, H. C. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
About the importance of the integration of biomechanical and physiological approaches and the application of modern technology as a tremendous potential to reveal new information concerning the factors the determine performance in c-c skiing, thereby helping to improve this performance.